Combined-information protein structure refinement: Potential energy-constrained real-space method for refinement with limited diffraction data - Fitzwater, Susan (1982)
A potential energy-constrained real-space refinement method designed for use with x-ray diffraction data of low to moderate resolution has been developed. The number of adjustable parameters is severely restricted to ensure a reasonable ratio of data to parameters. Only dihedral angles are allowed to vary; bond lengths and bond angles are fixed at physically reasonable values. The structure of bovine pancreatic trypsin inhibitor was refined by using this method with data to only 2.5-Å resolution. Both the R-factor and the electron-density map improved throughout the refinement, and the final structure was a satisfactory approximation to the 1.5-Å structure.